PEMBENTUKAN BUDAYA SEKOLAH DI LINGKUNGAN SMKN 3 PALANGKA RAYA UNTUK MENINGKATKAN KUALITAS KINERJA GURU-GURU PRODUKTIF - APRILIA, PRISKA; SUHARDI, MUHAMAD (VOCATIONAL: Jurnal Inovasi Pendidikan Kejuruan, 2023)
The role of teachers and schools is crucial in developing competent and competitive human resources. To produce graduates with high-quality human resources, teachers play a critical role in education and the learning process in schools. Currently, many schools and educational institutions are unaware of their school culture, resulting in no efforts for improvement or development of the school culture. Issues with school culture can lead to low student motivation and academic performance because the school does not become a conducive place for learning. This research aims to examine the school culture at SMKN 3 Palangka Raya and its role in the performance of productive teachers. This study is qualitative research in the form of a literature review related to: 1. School culture and its role in improving the performance of productive teachers; 2. the school culture at SMKN 3 Palangka Raya. School culture consists of habitual and ongoing activities that become the school’s identity. A positive school culture plays a role in enhancing the performance of productive teachers, which includes training on instrument creation and practical fieldwork. The school culture at SMKN 3 Palangka Raya, known as "Bajenta Bajorah," helps create a Child-Friendly School (CFS). To improve skills, the culture implemented by SMKN 3 Palangka Raya includes field trips, practical fieldwork, and a school literacy movement. ABSTRAKGuru dan sekolah memiliki peran dalam mengembangkan SDM yang kompeten dan mampu berdaya saing. Untuk dapat menghasilkan lulusan dengan SDM yang tinggi maka guru memiliki peran yang krusial dalam Pendidikan serta pembelajaran di sekolah. Saat ini, banyak sekolah dan Lembaga Pendidikan yang tidak menyadari budaya sekolahnya. Hal ini menyebabkan tidak adanya upaya perbaikan atau pengembangan budaya sekolah tidak terlaksana. Permasalahan budaya sekolah akan berdampak pada rendahnya motivasi belajar dan prestasi siswa karena sekolah tidak menjadi tempat yang kondusif untuk belajar. Penelitian ini bertujuan untuk Penelitian ini bertujuan untuk mengkaji budaya sekolah di SMKN 3 Palangka Raya dan perannya pada kinerja guru produktif. Penelitian ini merupakan penelitian kualitatif dalam bentuk kajian literatur terkait dengan: 1. Budaya sekolah dan perannya untuk meningkatkan kinerja guru produktif; 2. budaya sekolah di SMKN 3 Palangka Raya. Budaya sekolah merupakan kebiasaan dan kegiatan yang dilakukans secara terus menerus dan menjadi identitas sekolah. Budaya sekolah yang baik memiliki peran untuk meningkatkan kinerja guru produktif, budaya ini adalah pelatihan pembuatan instrument dan praktik kerja lapangan. Budaya sekolah di SMKN 3 Palangka Raya adalah Bajenta Bajorah sehingga mampu menciptakan Sekolah Ramah Anak (SRA). Dalam hal peningkatan keterampilan, Budaya yang diterapkan oleh SMKN 3 Palangka Raya adalah karyawisata, praktik kerja lapangan dan gerakan literasi sekolah.